Integrasi Pembelajaran Pendidikan Agama Islam Berwawasan Ekologi di Sekolah Menengah Pertama Bina Karya Surabaya - Mahmud, Amir; Maisyanah, Maisyanah; Rahman, Arif (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
Environmental issues often stem from the lack of public awareness of the surrounding environment. Because human behavior and the environment are closely related, it is very important to develop the character of environmental care through education. This factor is one of the challenges faced by educational institutions today. This research is motivated by the researcher's assumption of the learning process of ecological Islamic religious education at Bina Karya Surabaya Junior High School. This type of research is qualitative field. The data were collected through observation, interviews and documentation. For data analysis, researchers do by means of data reduction, data presentation, and consclucing drawing/verificaton. The research results are as follows: (1) Planning for ecological Islamic Education learning is realized in the form of a syllabus along with the development of lesson plans. (2) The implementation of ecological Islamic Education learning is carried out in accordance with the stages of implementing the discovery learning model (stimulation, problem statement, data collection, data processing, generalization), (3) Evaluation of ecological Islamic Education learning using authentic assessment which can be carried out by means of tests and non-tests.